2002
DOI: 10.1046/j.1464-410x.2002.03025.x
|View full text |Cite
|
Sign up to set email alerts
|

Does pericapsular lignocaine reduce pain during transrectal ultrasonography‐guided biopsy of the prostate?

Abstract: Objective To evaluate whether injection with pericapsular lignocaine before transrectal ultrasonography (TRUS)-guided biopsy reduces the perceived pain of prostatic biopsy. Patients and methods The study included 121 patients referred for TRUS-guided biopsy of the prostate; 27 underwent biopsy with no previous injection and 94 were randomized to pericapsular injection with either 1% lignocaine or a placebo (saline). Both patient and operator were unaware of the content of the injection. The injection was deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 15 publications
(18 reference statements)
2
30
0
1
Order By: Relevance
“…There were no severe complications that required hospitalization in any of the patients. Similarly, in several studies, it has been shown that the use of periprostatic blockage with an intrarectal gel is better than placebo (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Entonox, which is a gas anaesthetic material (50% nO and 50% O 2 mixture), is widely used in the UK during delivery, in minor procedures treating trauma, and in emergencies, because it provides short-term anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…There were no severe complications that required hospitalization in any of the patients. Similarly, in several studies, it has been shown that the use of periprostatic blockage with an intrarectal gel is better than placebo (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Entonox, which is a gas anaesthetic material (50% nO and 50% O 2 mixture), is widely used in the UK during delivery, in minor procedures treating trauma, and in emergencies, because it provides short-term anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…In two studies, a five-point pain scale was used and the scores in these studies were converted to a 10-point pain scale to facilitate comparison. 14,19 If the pain ratings in a study were taken at different times of the biopsy procedure, only the pain scores taken immediately at the end of the biopsy procedure were extracted for analysis. The secondary outcome measures were complications associated with the use of local anesthesia.…”
Section: Data Extractionmentioning
confidence: 99%
“…32,33 A total of 25 trials were eventually evaluated. 19,56,57 Trials identified as potentially relevant and screened (n= 61) Trials retrieved for detailed evaluation (n=42) Trials excluded as not relevant (n=19)…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations